Pengaruh Edukasi pada Siswa SMA Kelas X di Sekolah SMA Negeri 2 Jakarta tentang Faktor Risiko dan Pencegahan Diabetes Melitus Tipe 2 - Tjiu Shui Lian; Lydia Tantoso (Jurnal Pengabdian Ilmu Kesehatan, 2025)
The lack of adolescent awareness about T2DM risk factors and prevention necessitates educational interventions. Health education plays a crucial role in transforming complex information into structured and comprehensible knowledge, enabling students to integrate new concepts with existing understanding for more comprehensive comprehension. This study aims to examine the knowledge level of 10th-grade students at SMA Negeri 2 Jakarta regarding T2DM risk factors and prevention before and after educational intervention, as well as to assess the intervention's effectiveness. The research employs an analytical-experimental design with a pre-test and post-test approach involving 75 respondents selected through convenience sampling. Primary data was collected directly from respondents, including personal identification information and evaluation results from pre-test and post-test questionnaires on T2DM educational material. The study has obtained necessary permits and ethical clearance. Data analysis was conducted using the Wilcoxon test in SPSS. Results demonstrate significant knowledge improvement, with average scores increasing from 45.58 (74.7% in poor category) in the pre-test to 79.35 (61.3% in good category) in the post-test. Statistical analysis revealed a significant difference (p < 0.0001) with a mean score difference of 33.77 points. The study concludes that health education effectively and significantly enhances students' knowledge about T2DM risk factors and prevention.